Mapping global vulnerability index in mining sectors: A case study Moulares-Redayef aquifer system, southwestern Tunisia. (September 2016) - Khelif, Nadia; Jmal, Ikram; Bouri, Salem
Abstract: Contrary to the DRASTIC model grouping together the saturated and unsaturated zones to compute a global intrinsic vulnerability index, the global vulnerability index method incorporates both hydrogeological and hydrochemical data for a comprehensive index mapping for the saturated zones. This concept depends on the behavior and the uses of the groundwater. The main aim of this study is to propose a scientific basis for sustainable land use planning and groundwater management of the Moulares-Reayef aquifer, located in Southwestern Tunisia. The overexploitation of this aquifer causes the threat of groundwater quality by various sources of pollution. The global vulnerability index was applied in the Moulares-Reayef aquifer. The results show that the most favorable zones to pollutant percolation are situated along the wadis (Tabaddit, Zallaz, Berka, …) which are drained by continuous discharges. The global vulnerability values were correlated with nitrates values for validation. It revealed a significant correlation showing that high values of nitrates occurred in highly vulnerable zones with a value of 0.69 for the Pearson coefficient. The global vulnerability evaluation shows that the aquifer is characterized by high vertical vulnerability and high susceptibility. Highlights: Standard DRASTIC model could not accurately predict groundwater's pollution risk. New Hybrid method combining vertical and horizontal indexes improve vulnerability assessment. Global index provides a powerful tool to assess aquifer vulnerability.